Part VII – July 1968 - Papers - The Stress-Strain Rate Behavior of a Manganese Steel in the Temperature Range of the Ferrite-Austenite Transformation - H. W. Schadler (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1969)
The superplastic behavior of low carbon and manganese bearing steels has been evaluated. The results of elevated-temperature stress-strain rate and elongation tests are reported which indicate that high strain rate sensitivity (>0.5) and adequate elongations are achievable in ultrafine-grained steels 1 to 2 p, but at strain rates which are not commercially attractive. It has been demonstrated that the fine grain size is retained after long times and high strains if the temperature is kept within the range of the two-phase (a + ?) field. INTEREST in superplasticity has been stimulated by the desire to: 1) understand the origin of, and mechanisms responsible for, the large uniform elongations observed, and 2) exploit this property for commercial advantage in metal forming operations. Although the Zn-22 wt pct Al alloy presently being studied as a model material1-5 may find application in sheet forming and extrusion, the potential of super-plasticity should best be realized in large tonnage materials, such as steel and aluminum alloys. The degree of superplasticity in low-carbon and manganese-bearing steels has been evaluated. The results of elevated-temperature stress-strain rate and elongation tests on ultrafine grain size material are reported. Avery and Backofen6 and Hart7 have shown that geometrically stable flow leading to extensive uniform elongation in the tension test is associated with high values of the strain rate sensitivity, m, defined: Lozinsky had reported that titanium and zirconium experience permanent deformation if subjected to a constant load and cyclic heating through the temperature range of the phase transformation. Although strain rate sensitivities in excess of about 0.2 had not been reported previously for steel, permanent deformation had been observed11-13 in a wide variety of steels subjected to a constant load and cyclic heating through the temperature range of the a-? phase transformation. Thus by analogy, steel could be expected to exhibit high strain rate sensitivity but only in the a + ? condition. High strain rate sensitivity has been observed at 650°C (a + Fe3C), but not reported as such, by Bailey, Dickenson, and pearson14 in 1931 at a strain rate of about 10-9 per min. It then remained to determine whether high tensile elongations would be observed in a rate-controlled test at constant temperature and at what strain rate strain rate sensitivity values greater than 0.5 would be observed. Since previous experience8 had indicated the importance of fine grain size to realizing high m at reasonable strain rates, it was first necessary to produce an ultrafine grain size and then keep the grains from growing during the test. The results of this investigation show that fine grain size can be readily produced16 and maintained by restricting the temperature of testing to below the ? transus. Further, superplasticity (high m and large uniform elongation) is observed. However, the strain rate range is only marginally useful for commercial forming operations with the finest grain size produced. MATERIAL The material investigated initially was a 1.9 wt pct Mn, 0.42 wt pct C, hot-rolled bar previously used by Low and Turka1015 and available in the laboratory. The 0.500-in. round was cold-rolled to a 0.090-in. flat, annealed for 4 hr at 850°C in argon, air-cooled, and cold-finished to 0.050 in. Subsequently, four additional steels of the compositions given in Table I were investigated to explore the effects of manganese, carbon, and test temperature on the observed stress-strain rate behavior. These steels were melted under argon, cast to 0.75 by 2 by 5 in. slabs, hot-rolled at 850°C, surface-finished to 0.13 in., and cold-finished to 0.050 in. Sheet tensile specimens 0.200 in. x thickness with 1- or 2-in. gage length were cut parallel to the rolling direction. Table I also includes the nominal transformation temperatures for the AISI 1340 and the four experimental steels. EXPERIMENTAL PROCEDURE Production of Fine Grain Size. Ultrafine grain size (1 to 5 p) was considered essential for this studv. Grange16 has described two techniques for producing